Spinal meningioma: clinical profile and outcome of surgical management (2022)
Spinal meningiomas are relatively rare tumors with often favorable surgical outcomes. There is a paucity of data on spinal meningiomas in the Nigerian literature. This study was designed to evaluate the incidence, anatomical distribution, and outcome of surgical treatment of spinal meningiomas at our center. This was a retrospective study of patients who underwent surgery for spinal meningioma during the study period. Data were obtained from case notes, operation, and pathology registers. Univariate analysis was performed using SPSS version 15 (SPSS Science Inc, Chicago, IL, USA). There were 11 patients in the study, all females, with an age range of 26–65 years. All patients presented with motor deficits. Four patients (36.4%) presented within six months of symptom onset, while symptom duration exceeded one year in five patients (45.5%). Preoperative functional grading was Frankel A in 2 patients (18.2%), Frankel B and C in 4 patients each (36.4%), and Frankel D in 1 patient (9.1%). Tumor locations were thoracic in six patients (54.5%), cervical in 2 patients (18.2%), and cervicothoracic in 3 patients (27.3%). All patients underwent gross total tumor resection. Postoperative neurological improvement occurred in 7 patients (63.6%), while 4 patients (36.4%) remained neurologically unchanged. Gross total tumor resection was achieved in all cases with satisfactory functional outcomes.